(untitled) (LACCEI, 2024)
Nowadays, there is a growing concern about the environmental impact of the use of non-biodegradable materials such as plastic for the production of bags and packaging. Therefore, it is essential to look for alternatives, such as the use of natural fibers from fruits or vegetables, specifically coconut shells. This material is sustainable and the way in which its use is proposed is as ecological packaging, since it would help protect the environment by avoiding environmental pollution. The present study analyzed the physical, chemical and mechanical properties of coconut fiber to determine a process for manufacturing eco-friendly packaging. In addition, tests were conducted to observe how well the fiber absorbs and elongates in different random samples. This information helped to create a prototype of an ecological packaging made with coconut fiber. As a result, it was found that this is an optimal type of fiber to produce ecological packaging because it is easily absorbed and stretched, has a high resistance to mechanical forces and can also be degraded by bacteria, which makes it a good option for the storage and packaging of objects due to the benefits offered by the use of coconut fiber.